Ecological risk assessment of impacted estuarine areas: integrating - Gonçalves, Cátia (2014)
The analysis of multiple biomarker responses is nowadays recognized as a valuable tool to circumvent potential confounding factors affecting biomonitoring studies and allows a better understanding of the mechanisms underlying exposure to natural mixtures of toxicants. For the purpose of an environmental risk assessment (ERA) in an impacted estuary in SW Europe (the Sado, Portugal), juvenile Solea senegalensis from commercial fishing areas were surveyed for histopathological liver alterations and biochemical biomarkers. Although the findings revealed moderate differences in the patterns of histopathological traits between urban/industrial- and agricultural-influenced areas within the same estuary, no significant distinction was found between the cumulative alterations in animals from the two sites. The overall level of histopathological injury was low and severe traits like neoplasms or preneoplastic foci were absent. While metallothionein induction and lipid peroxidation could relate to histopathological condition indices, the activity of anti-oxidant enzymes appeared to be impaired in animals collected off the estuary's heavy-industry belt (the most contaminated site), which may partially explain some degree of hepatic integrity loss. Overall, the results are consistent with low-moderate contamination of the estuary and indicate that oxidative stress is the most important factor accounting for differences between sites. The study highlights the need of integrating multiple biomarkers when multiple environmental stressors are involved and the advantages of surveying toxicity effects in fieldcollected, foraging, organisms.